2006
DOI: 10.1161/01.hyp.0000230610.81947.04
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hypertension 5 Years After Stroke in the North East Melbourne Stroke Incidence Study

Abstract: Abstract-Control of blood pressure after stroke is important for reducing the risk of recurrent stroke. We examined the control of hypertension in a community-based population of 5-year stroke survivors. Cases of first-ever stroke from the North East Melbourne Stroke Incidence Study were interviewed at 5 years poststroke. Blood pressure, history of hypertension, and antihypertensive medications were recorded. Individuals were classified as normotensive (blood pressure Ͻ140/90 mm Hg, no history of hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…2 The NEMESIS study in Australia examined blood pressure control at five years post-stroke. 23 About 450 patients were evaluated in the study, but only 300 of them had complete data (blood pressure measurement, medication records, and survey). Results showed that 82% of the patients were diagnosed with hypertension; 52% were controlled (90% on therapy), and 30% were uncontrolled (67% on therapy).…”
Section: Dyslipidemia and Hypertension Managementmentioning
confidence: 99%
“…2 The NEMESIS study in Australia examined blood pressure control at five years post-stroke. 23 About 450 patients were evaluated in the study, but only 300 of them had complete data (blood pressure measurement, medication records, and survey). Results showed that 82% of the patients were diagnosed with hypertension; 52% were controlled (90% on therapy), and 30% were uncontrolled (67% on therapy).…”
Section: Dyslipidemia and Hypertension Managementmentioning
confidence: 99%
“…4,5 Presently, for secondary prevention of stroke, achieving a target BP of 130/80 mm Hg with a combination of any available antihypertensive drugs is recommended. [5][6][7][8][9] Despite this, there is consistent evidence to suggest that BP is poorly controlled in a proportion of this high-risk as long as 5 years after stroke. [7][8][9] The North East Melbourne Stroke Incidence Study (NEMESIS) trial reported that 37% of hypertensive 5-year stroke survivors had above target BP readings, and that 18% were not taking any antihypertensive medications.…”
Section: Stroke and Blood Pressure Loweringmentioning
confidence: 99%
“…[5][6][7][8][9] Despite this, there is consistent evidence to suggest that BP is poorly controlled in a proportion of this high-risk as long as 5 years after stroke. [7][8][9] The North East Melbourne Stroke Incidence Study (NEMESIS) trial reported that 37% of hypertensive 5-year stroke survivors had above target BP readings, and that 18% were not taking any antihypertensive medications. 9 Although the reasons for poor BP control in this population are likely to be complex, emergent populations of both difficult-to-treat and resistant hypertensives are likely to contribute to this effect, 10 as is the side-effect profile associated with commonly prescribed antihypertensives.…”
Section: Stroke and Blood Pressure Loweringmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimate was based on evidence in the literature for prevention programs that have no additional Medicare incentive payments (eg, practice nurse payments). 22 …”
Section: Estimating the Number Of Strokes Preventedmentioning
confidence: 99%